Keikutsertaan Mahasiswa KKN Kolaboratif dalam Survei Anak Tidak Sekolah (ATS) di Kabupaten Jember - Reinka Sekar; Natasha Angelina Susilo; Tiara Fibrianti Ning Tyas; Khiftia Rachmah Hidayah; Virginia Mandasari (Universitas Negeri Surabaya, 2026)
The purpose of this study is to analyze the participation of Collaborative KKN #3 students in reducing the dropout rate through a survey of Out-of-School Children (ATS) in Jember District. The research method includes collecting data from various sources through interviews conducted with residents of Jember District and direct practical interactions by Collaborative KKN 3 students. The results of the analysis of the system used in recording out-of-school children use the website from Jember District which can be accessed by KKN students to record the truth of the data of out-of-school children. The survey results show three main factors that cause children to drop out of school: 1) Economic Factors, 2) Early Marriage, and 3) Moving to Islamic Boarding Schools.